(untitled) (Polis (Santiago), 2024)
This paper presents a methodological proposal whose purpose is to contribute, from experience, to the field of participatory action research with social organizations. We see this as a powerful approach for dialogue and the co-construction of knowledge between the public university and communities, aimed at transforming the realities they inhabit. The article combines descriptions and theoretical and empirical positions that have arisen and been built in the investigative process, around the central axis: the methodological plot, made up of different moments that guide and give substance to action research. The experience that gave life to the methodological plot consisted of a research work in which the socio-political organizational process of the “Coletivo de Trabajadorxs Sexuales - AMMAR (Asociación de Mujeres Meretrices de la Argentina) Río Cuarto” was reconstructed, from its formation (2015) until the year 2022, with emphasis on iconic moments of its development, such as its creation, the passage through the Covid-19 pandemic and the incorporation/affiliation to AMMAR. We share a brief summary of this experience.